Motorcycle Crash Prediction Model for Non-Signalized Intersections - Sulistio, Harnen; Radin Sohadi, Radin Umar; Wong, Shaw Voon; Wan Ibrahim, Wan Hashim (2003)
This paper attempts to develop a prediction model for motorcycle crashes at non-signalized on urban roads in Malaysia. The Generalized Linear Modeling approach was used to develop the model. The final model revealed that an increase in motorcycle and non-motorcycle flows entering an intersection is associated with an increase in motorcycle crashes. Approach speed. Lane width, number of lane, shoulder width and land use were also found to be significant in explaining motorcycle crashes. The model assist traffic engineers to decide the need for appropriate intersection treatment that specially designed for non-exclusive motorcycle lane facilities.